2021
DOI: 10.1155/2021/6109406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on Diabetic Kidney Disease: A Systematic Review and Meta-Analysis of Randomized, Double-Blind, Placebo-Controlled Clinical Trials

et al.

Abstract: Background. Curcumin, a polyphenolic constituent from Curcuma longa, possesses antioxidant, hypolipidemic, and antidiabetic properties and has been reported to protect against diabetic kidney disease (DKD); however, the effect is inconsistent. Objective. This systematic review and meta-analysis aimed to investigate the effect of curcumin supplementation on renal function, lipid profile, blood pressure, and glycemic control in DKD. Methods. A systematic and comprehensive literature search of interrelated random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Fatih et al demonstrated, in a preclinical I/R study, that the use of curcumin reduced inflammatory process, oxidative stress and apoptosis by the semaphorin–plexin [ 30 ]. In a translational view, a meta-analysis of randomized, double-blind, placebo-controlled clinical trials about curcumin supplementation in patients with diabetic kidney disease (DRD) showed a significant improvement in serum creatinine corroborating the findings of this investigation [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 66%
“…Fatih et al demonstrated, in a preclinical I/R study, that the use of curcumin reduced inflammatory process, oxidative stress and apoptosis by the semaphorin–plexin [ 30 ]. In a translational view, a meta-analysis of randomized, double-blind, placebo-controlled clinical trials about curcumin supplementation in patients with diabetic kidney disease (DRD) showed a significant improvement in serum creatinine corroborating the findings of this investigation [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 66%
“…Curcuma Longa Linn, of the Zingiberaceae family, contains a structure called rhizome, which is converted into a powder, known as turmeric, from which a natural component named curcumin is derived. Curcumin is part of the polyphenol group, known primarily for its use as a culinary spice [ 84 , 85 , 86 ]. It has many known biological roles that may influence the treatment of several oncological, neurological, cardiological and nephrological conditions [ 87 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
“…It has many known biological roles that may influence the treatment of several oncological, neurological, cardiological and nephrological conditions [ 87 ]. Curcumin can modulate inflammation, the immune system, lipid and carbohydrate metabolism and prevent the development of DM-derived complications, including DKD [ 84 , 88 ]. It also plays a role in decreasing OS [ 7 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TCM, nutraceuticals derived from Chinese herbal medicines could prevent DKD, for example, boswellic acid, curcumin and quercetin ( Lu et al, 2015 ; Lu et al, 2017 ; Asgharpour and Alirezaei, 2021 ). A systematic review and Meta-analysis revealed that curcumin supplementation significantly improved blood sugar, lipid and blood pressure control and decreased the serum creatinine in DKD patients ( Jie et al, 2021 ). Lu et al also found that curcumin could delay fibrosis progression in DKD mice by inhibiting the initiation of NLRP3 inflammasome and reduce the expression of IL-1β in renal tissue ( Lu et al, 2017 ).…”
Section: Anti-inflammation Treatment In Dkdmentioning
confidence: 99%